Contribution Of Young Entrepreneurs In Building The Creative Economy Of Village Communities - Latif Syaipudin (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
Young entrepreneurs are important figures in economic development, especially at the village level, which are expected to encourage the development of the creative economy. The figure of a young entrepreneur will give more colour to developing a creative economy in a village. The purpose of this study is to analyze the contribution of young entrepreneurs in encouraging the development of the creative economy in Latuka villages, with the specific aim of examining the factors that influence it. This research method is descriptive qualitative data collection techniques using observation, documentation, and unstructured interviews. The informants comprised 34 young entrepreneurs whose average age range was 17-30 years. The findings of this study indicate that young entrepreneurs impact the development of the creative economy. At least four factors intersect in developing the creative economy for young entrepreneurs, namely environmental, socio-economic, risk-taking, and social media factors. The contribution of this research can strengthen the concept of developing a creative economy, especially among young people, and make it one of the concerns for stakeholders to pay more attention to young entrepreneurs in villages.